Bacterial Pathogens Isolated from Patients with Bloodstream Infection: Frequencies of Occurrence and Antimicrobial Susceptibility Patterns from the SENTRY Antimicrobial Surveillance Program (United States and Canada, 1997) - Pfaller, Michael A. (American Society for Microbiology, 1998)
The SENTRY Program was established in January 1997 to measure the predominant pathogens and antimicrobial resistance patterns of nosocomial and community-acquired infections over a broad network of sentinel hospitals in the United States (30 sites), Canada (8 sites), South America (10 sites), and Europe (24 sites). During the first 6-month study period (January to June 1997), a total of 5,058 bloodstream infections (BSI) were reported by North American SENTRY participants (4,119 from the United States and 939 from Canada). In both the United States and Canada, Staphylococcus aureus and Escherichia coli were the most common BSI isolates, followed by coagulase-negative staphylococci and enterococci. Klebsiella spp., Enterobacter spp., Pseudomonas aeruginosa, Streptococcus pneumoniae, and β-hemolytic streptococci were also among the 10 most frequently reported species in both the United States and Canada. Although the rank orders of pathogens in the United States and Canada were similar, distinct differences were noted in the antimicrobial susceptibilities of several pathogens. Overall, U.S. isolates were considerably more resistant than those from Canada. The differences in the proportions of oxacillin-resistant S. aureus isolates (26.2 versus 2.7% for U.S. and Canadian isolates, respectively), vancomycin-resistant enterococcal isolates (17.7 versus 0% for U.S. and Canadian isolates, respectively), and ceftazidime-resistant Enterobacter sp. isolates (30.6 versus 6.2% for U.S. and Canadian isolates, respectively) dramatically emphasize the relative lack of specific antimicrobial resistance genes (mecA, vanA, and vanB) in the Canadian microbial population. Among U.S. isolates, resistance to oxacillin among staphylococci, to vancomycin among enterococci, to penicillin among pneumococci, and to ceftazidime among Enterobacter spp. was observed in both nosocomial and community-acquired pathogens, although in almost every instance the proportion of resistant strains was higher among nosocomial isolates. Antimicrobial resistance continues to increase, and ongoing surveillance of microbial pathogens and resistance profiles is essential on national and international scales.